‘David found Ziklag burned with fire’: Assessing ecoterrorism in a multireligious Nigeria - Uroko, Favour C. (Theologia Viatorum (Sorenga), 2023)
This article examines the phenomenon of ecoterrorism in Nigeria and the roles of faith-based communities in curbing ecoterrorism. In Nigeria, there have been numerous cases of ecoterrorism, committed by Fulani herdsmen against the indigenous populations. Literature has laid emphasis on ecoterrorism, with its implications for faith-based organisations (FBOs) sidelined. The phenomenon of ecoterrorism started in the Old Testament, when David and his men burned Ziklag with fire, destroying the houses, farmlands, and other properties there. From the documentary analysis, findings reveal that there are divergent reasons given for the prevalence of ecoterrorism in Nigeria. Firstly, it is believed that the Fulani herdsmen have the ambition of taking over the lands of non-Fulani people. Secondly, it is alleged, especially by Christians, that the ecoterrorism that is being carried out by Fulani herdsmen is an attempt to enforce Islam on the entire populace. Thirdly, a lack of education on pastoralism has sustained ecoterrorism in Nigeria. Also, the results indicate that ecoterrorism affects women, children, and property more than any terrorist attack. Recommendations are discussed.ContributionEcoterrorism is one of the leading factors of poverty, famine, and abuse in Nigeria, and it also affects farmers, especially those in rural areas. Practical theology was implicated in this study.